Bernardino Pardo and his wife Dolores Gil, photographers - Agustín Lacruz, Carmen; Clavero Galofré, Manuel (Revista General de Información y Documentación, 2019)
Until recently in Spain, the names and surnames of the photographers were ignored or unknown in the photography history texts. However, during the second half of the nineteenth century, a significant part of women photographers were professional partners with their husbands, also photographers. The most known marriages were those of Mr. Fernando y Anaïs Napoleón; Ludovisi y Señora; Poujade y señora; José Villalba y Señora; F. Prosperi y Señora and to a lesser extent, the couple formed by Dolores Gil and Bernardino Pardo, who toured the northeast of Spain, working as traveling photographers from the mid-1860s, until they opened a studio in Zaragoza in 1871 in the populous neighborhood of San Pablo. This article analyzes the photographic activity of Dolores Gil and Bernardino Pardo and identifies and describes the characteristics of his work. The study has been carried out through the systematic review of the sources of bibliographic information located to date, as well as through the analysis of new hemerographic and archival sources. The main results are the elaboration of his biographies, the contextualization of his professional trajectories and the inventory of his works.